The fish fauna of the four rivulets of Börzsöny and Pilis mountains with together Gödöllő Hill - Keresztessy, Katalin; Bardóczyné Székely, Emőke (Acta Agraria Debreceniensis, 2007)
Occurence of fish species were examined in four rivulets of Börzsöny, Pilis mountains and Gödöllő hill. Althogether 28 fish species were subject in research, of which 9 are protected.